Effects of game‐based learning on students' mathematics achievement: A meta‐analysis - Tokac, Umit; Novak, Elena; Thompson, Christopher G. (Journal of computer assisted learning, 2019)
This meta‐analysis investigated the effects of learning video games on mathematics achievement of PreK‐12th‐grade students compared with traditional classroom instructional methods. Results from the 24 collected studies showed heterogeneity among effect sizes, both in magnitude and direction. Using a random effects model, a small but marginally significant overall effect ( d¯RE=0.13,p=.02) suggested that mathematics video games contributed to higher learning gains as compared with traditional instructional methods. In addition, moderator analyses were mixed in terms of statistical significance and explored effect‐size heterogeneity across effects using grade level, instrument type, length of game‐based intervention, country, publication type, and study year characteristics. Overall findings indicate that video games are a slightly effective instructional strategy for teaching mathematics across PreK‐12th‐grade levels. Lay Description What is already known about this topic: Math video games are gaining increased popularity in the classroom. Research on the effectiveness of math video games in PreK‐12 education is inconsistent. More empirical studies on math video games are needed. What this paper adds: This meta‐analysis focused on math video games versus traditional classroom instruction. The targeted learner audience was PreK‐12 students. The target learning outcome was mathematics achievement. Results indicate that video games contribute to higher learning gains compared with traditional instruction. Publication year and type influenced the strength of the video‐gaming intervention effect. Implications for practice and/or policy: Video games are an effective instructional strategy for teaching mathematics across PreK‐12th grades. Having more teaching instruction/intervention that includes video games might increase students' math achievement.